KUALITAS PROGRAM PELAYANAN SI MELIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BULELENG - Suyeni, I Gusti Ayu Vinna Rai; Winaya, I Ketut; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2024)
The Population and Civil Registration Office of Buleleng Regency issued an innovative public service program called SI MELIK, which in this program is carried out using service cars that come directly to villages in each sub-district in Buleleng Regency. The purpose of this study was to determine the service quality of the SI MELIK Program at the Population and Civil Registration Office of Buleleng Regency. This study uses descriptive qualitative methods with data collection techniques in the form of observation, interviews, documentation. Based on the study of Service Quality Theory according to Zeithaml, Parasuraman, and Berry, it was found that the quality of this program has been running well but is still not optimal, such as Tangible, Reliability, Responsive, Assurance, and Empathy this deficiency occurs because there is still a lack of checking the device to be used and the internet network which is sometimes not available in certain villages.